1998
DOI: 10.1046/j.1537-2995.1998.38998408999.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of infectivity in blood components and plasma derivatives in experimental models of transmissible spongiform encephalopathy

Abstract: Convergent results from exogenous spiking and endogenous infectivity experiments, in which decreasing levels of infectivity occurred in cellular blood components, plasma, and plasma fractions, suggest a potential but minimal risk of acquiring Creutzfeldt-Jakob disease from the administration of human plasma protein concentrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
245
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(261 citation statements)
references
References 17 publications
14
245
0
2
Order By: Relevance
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies revealed that prion infectivity titres of blood samples harvested during the asymptomatic phase of prion disease were up to 10-fold less than those collected during the clinical phase [10,19,20,22]. Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In an attempt to establish the distribution of infectivity in blood, normal human blood was spiked with scrapie-infected hamster brain homogenate [38]. This showed that the highest concentration of infectivity was in the cellular blood components, with lower levels in plasma, cryoprecipitate and Cohn fractions I-III, with almost none detected in fractions IV and V [38].…”
Section: Evidence For Infectivity In Blood In Prion Diseasesmentioning
confidence: 99%